OBSTACLES OF THE PROSECUTOR IN DETERMINING CRIMINAL PROSECUTIONS AGAINST CRIMINAL ACTS OF CORPORATE CORRUPTION - Asmadila Aqil Syahputri; Fauzul Aliwarman (Universitas Islam Balitar, 2022)
This study aims to determine the barriers to prosecution of criminal acts of corporate corruption in accordance with the development of existing laws and regulations and to find out the obstacles to its application in real life. This research is an empirical legal research, using the law approach, interview approach, and data collection approach. corporations as legal subjects are in modern society, the role of corporations is very strategic, even in practice it can be a means to commit crimes (corporate criminals) and profit from the proceeds of crime (crimes for corporations) therefore to protect the public and provide legal certainty in the enforcement process. Government law seeks to regulate corporations as legal subjects in dealing with the public and other corporations. Corporations are legal subjects who can be held accountable but in practice there are still many obstacles to law enforcement in determining the prosecution of criminal acts of corporate corruption. Those obstacles. With the issuance of Supreme Court Regulation No. 13 of 2016 corporations can be held accountable for corruption crimes committed by management or corporate organs.